Clinical Efficacy Of Medical Dextrose Tincture Liquid In The Treatment Of Facial Photoaging - Song, Yuexing; Liu, Qiuhui; Zhang, Yihan; Zhang, Huina; Li, Bin (Dermatology Practical & Conceptual, 2023)
Objectives: The purpose of this study was to explore the clinical efficacy of medical dextrose tincture liquid (medical dextrose tincture) in the treatment of facial photoaging. Methods: Thirty-four volunteers were included in the randomized double-blind study. According to the random number table method, the subjects were randomized into control and treatment groups. The subjects in the control and treatment groups were treated with medical hyaluronic acid gel and medical dextrose tincture, respectively. They received three times of mesotherapy therapy with an interval of 28 days. Video image acquisition was performed before treatment and 28 days after treatment. Skin moisture content, glossiness, heme content, collagen density, and elasticity were tested. The subjective evaluation of subjects and doctors before and after treatment were compared. Results: Compared with before treatment, medical dextran tincture significantly increased the skin moisture retention, skin gloss, and skin collagen density (p<0.001). Additionally, the skin retraction time was significantly reduced, and the skin retraction time was also markedly decreased after treatment with medical dextran tincture (p<0.001). The effects of medical dextran tincture were more significant in comparison with medical hyaluronic acid gel (p<0.05). The subjective evaluation results of doctors showed that after 84 days of treatment, the overall skin photoaging score was significantly reduced (p<0.001). The subjective evaluation results of volunteers showed that the various skin problems of more than 50% of volunteers were improved after treatment. Conclusion: Medical dextran tincture has obvious effects of moisturizing, increasing luster, improving skin redness, increasing skin collagen content and enhancing skin elasticity.